Modeling of gravity-designed RC sub-assemblages subjected to lateral loads. (1st January 2017) - Laterza, Michelangelo; D'Amato, Michele; Gigliotti, Rosario
Highlights: Numerical models for seismic assessment of old RC existing sub-assemblages are proposed. Modeling criteria are defined only on geometrical and mechanical elements properties, without calibration process. Cyclic nonlinear analyses are conducted on gravity-designed RC structures. Comparisons with experimental results validate the proposed models for the sub-assemblages considered. Abstract: This paper aims to propose numerical models for seismic assessment of old existing RC beam-column sub-assemblages. In particular, two modeling approaches are described: for internal (usually named "C joints") and for external (named "T joints") beam-column sub-assemblages, both designed only for vertical loads without reinforcing details rules (such as inadequate bars lap splice, absence of hoops within the joint panel). They were developed starting from the failure mechanisms observed during an experimental campaign carried out on specimens reproducing old existing RC sub-assemblages cast in full and reduced scale, as well as reinforced with smooth longitudinal bars. The proposed models are not time-consuming with respect to both modeling and computational efforts, and do not require any calibration procedure from an experimental data set. They may be easily implemented in a general-purpose finite element program since merely based on geometrical and mechanical properties of RC elements. The numerical predictions show a good agreement with the experimental ones demonstrating that the proposed models are able of reproducing the lateral response of the two considered sub-assemblages typologies, in terms of both failure mechanism and hysteretic dissipative capacity.